Photochemical Behavior of Some Estrone Aryl and Methyl Sulfonates in Solution: Preparative and Mechanistic Studies - Quindt, Matías Iván (2021)
Direct irradiation of estrone aryl and methyl sulfonates in different organic solvents under nitrogen atmosphere was investigated under steady-state conditions. The estrone derivatives reacted efficiently through the photo-Fries rearrangement reaction involving [1;3]-sulfonyl migration providing the ortho-sulfonyl estrone derivatives and estrone as the photoproducts. In addition, estrone and 2-arylsulfonyl estrone derivatives were epimerized involving a Norrish Type-I reaction. Chemical quenching and photosensitization experiments on the photoreaction have been also carried out to establish the photoreactive excited state. Likewise, the solvent effect and the nature of the sulfonyl group on the photoreactions have been also studied.